Sustaining performance habitats for balinese animal effigies in the anthropocene - Hood, Made Mantle (University of Malaya, 2015)
Performance contexts for the barong, a mythical animal effigy that symbolizes a Balinese Hindu community's protective spirit, include mock-purification rituals, professional music and dance competitions, and a revival of children's busking barong as street entertainment. In each context, anthropomorphized mythical animals such as boars, tigers, and elephants perform meanings and beliefs that exist along a continuum from revered deity to superficial symbol. In this essay, I draw upon discourses surrounding music ecology and environmental sustainability which serve as background for citing correlations between the physical destruction of Bali's natural environment and urbanization's influence on the mythical animal's traditional performance habitat.